IMPROVING THE PRODUCTIVITY OF THE EQUIPMENT BY IMPROVING THE SEED COMB OF THE 4DP-130 CHAINSAW (Journal of Science-Innovative Research in Uzbekistan, 2024)
4 DP-130 chain saws have been improved to improve the efficiency of the seed comb